PROSES BERPIKIR KREATIF MATEMATIK PESERTA DIDIK MENURUT WALLAS DALAM MENYELESAIKAN MASALAH OPEN ENDED DITINJAU DARI GAYA BELAJAR VISUAL - Herni Indriastuti; Nani Ratnaningsih; Nurfadilah Siregar (Jurnal Dedikasi Pendidikan, 2021)
The purpose of this study was to describe the creative thinking process of students according to Wallas in solving "Open-Ended" problems in terms of visual learning styles. The research method used by qualitative exploratory research method.  The results of this study indicate that: (1) Students who have a visual learning style can meet all indicators of the creative thinking process of mathematics according to Wallas' stage in completing an open-ended well, namely in the preparation, incubation and illumination stages.  (2) Students who have a visual learning style generally tend to have a high creative thinking process in solving the given open-ended problem test questions. This research implies that teachers are expected to apply learning by using learning methods that are by the learning styles of students to improve the creative thinking process of students in solving problems optimally.